1969
DOI: 10.1042/bj1140477
|View full text |Cite
|
Sign up to set email alerts
|

A purification and some properties of an insecticidal exotoxin from Bacillus thuringiensis Berliner

Abstract: An insecticidal exotoxin from Bacillus thuringiensis var. thuringiensis (Berliner) has been purified. The efficiency of each stage of the purification has been ascertained and the yield of toxic material estimated by means of a quantitative bioassay. It is shown that the exotoxin is an adenine derivative substituted at position 9 and having a molecular weight of approximately 825. It can be dephosphorylated enzymically or chemically under conditions that define the exotoxin as a phosphomonoester. This results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…This is an insecticidal adenine-nucleotide analogue with a molecular weight of 701 Da (Bond et al, 1969). Toxicity of the b-exotoxin is probably due to inhibition of DNA-directed RNA polymerases by competition with ATP, inhibiting the synthesis of RNA (Sebesta and Horska, 1970;Vankova, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…This is an insecticidal adenine-nucleotide analogue with a molecular weight of 701 Da (Bond et al, 1969). Toxicity of the b-exotoxin is probably due to inhibition of DNA-directed RNA polymerases by competition with ATP, inhibiting the synthesis of RNA (Sebesta and Horska, 1970;Vankova, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…b-exotoxin is a secreted thermostable adenine nucleotide analogue of low molecular weight (701 Da) that is toxic to a wide range of insect species (Bond et al, 1969;de Barjac and Dedonder, 1965;Farkas et al, 1969). Levinson et al (1990), using high-performance liquid chromatography (HPLC), described two types of b-exotoxin (types I and II).…”
mentioning
confidence: 99%
“…Although other insects bioassay systems could be used, fly (Musca domestica) bioassays may be superior for the detection of b-exotoxin activity (see discussion in Levinson et al (1990)). Ohba et al (1981) reported a qualitative fly bioassay based on filter paper impregnated with autoclaved culture supernatant, but most fly bioassays are performed by mixing autoclaved culture supernatant with diet ingredients that are added to support larval growth and development (Bond and Boyce, 1971;Bond et al, 1969;Ignoffo and Gard, 1970;Johnson et al, 1998;Levinson et al, 1990). Although there is not a generally accepted or standard fly bioassay, it is noteworthy that two WHO guidelines (WHO, 1999(WHO, , 2007 state that detection of b-exotoxin should be done using the diet-based methods of Bond and Boyce (1971).…”
mentioning
confidence: 99%
See 2 more Smart Citations